EFEKTIVITAS OTAGO EXERCISE PROGRAMME SETELAH SENAM LANSIA TERHADAP RISIKO JATUH PADA LANSIA DI PSTW BUDI MULIA I - ACHIRDA, NUR; KURNIAWATI, NIA; AMINOTO, TOTO; SAURULITA, ANGELA; LINA, RATU KAREL (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Background: Elderly are someone who vulnerable to decline health status and physical abilities. One of changes in physical conditions that interfere with daily activities elderly is risk of falling. Objective: To determine effectiveness of Otago Exercise Program and elderly exercise to reduce risk of falls in elderly at Tresna Werdha Budi Mulia I Social Home. Method: This research uses quasi-experimental research design with prepost-test two group design, for 3 weeks, 2 times a week. The research respondents consisted 22 people, 11 people as treatment group with Otago Exercise Program intervention and elderly exercise, and 11 people as elderly exercise control group, timed up and go test was measured before and after intervention was given to measure the risk of falls. Results: The Paired Sample T-Test showed a p 0.000 in Otago Exercise Program intervention and elderly exercise, while the Wilcoxon Test results for the elderly exercise control group obtained a p 0.003. Conclusion: Intervention of the Otago Exercise Program and elderly exercise has more significant effect on reducing risk of falls in elderly people who experience balance disorders compared to providing elderly exercise.